Preventing ergonomic risks with integrated planning on assembly line balancing and parts feeding. Issue 24 (17th December 2017) - Battini, Daria; Calzavara, Martina; Otto, Alena; Sgarbossa, Fabio
Abstract : In this paper, we advise to perform assembly line balancing simultaneously with decision-making on parts feeding. Such integrated planning may open additional potential to reduce labour costs. Additional planning flexibility gained with the integrated planning may be used to mitigate ergonomic risks at workplaces. We formulate the integrated assembly line balancing and parts feeding planning problem, propose a mixed-integer model and compare integrated planning to a common hierarchical planning approach in a detailed case study on the assembly of a self-priming pump. Our case study illustrates that workplaces with high ergonomic risks may emerge even in productions that involve handling parts and workpieces of low weights and avoid static and awkward postures. We also show that the proposed integrated planning approach may eliminate excessive ergonomic risks and improve productivity indicators simultaneously.